2021
DOI: 10.3311/ppci.18406
|View full text |Cite
|
Sign up to set email alerts
|

Creep Properties of Expansive Soils under Triaxial Drained Conditions and its Nonlinear Constitutive Model

Abstract: The creep behaviors of expansive soils play an important role in landslide prediction and long-term stability analysis. In this paper, triaxial drained compression creep tests of expansive soils were conducted on the improved stress-controlled triaxial apparatus. The test results show that only transient deformation and attenuation creep occur with low deviator stress, and the increment of axial strain increases exponentially with deviator stress increasing; while deviator stress reaches a certain value, atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Yang et al [7] carried out creep tests under different perimeter pressures on cured blowfill mud-consolidated soil and established a prediction formula that reflected the creep characteristics of mud-consolidated soil. Li et al [8] conducted a triaxial unloading creep test on expanded soil and proposed a nonlinear four-element creep model, which described the evolution of the axial strain of expanded soil over time, under triaxial compressive stress and under equal circumferential pressure, by comparing the experimental results with the simulation results. Li et al [9] conducted a triaxial unloading creep test on artificially frozen soil and described its creep characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [7] carried out creep tests under different perimeter pressures on cured blowfill mud-consolidated soil and established a prediction formula that reflected the creep characteristics of mud-consolidated soil. Li et al [8] conducted a triaxial unloading creep test on expanded soil and proposed a nonlinear four-element creep model, which described the evolution of the axial strain of expanded soil over time, under triaxial compressive stress and under equal circumferential pressure, by comparing the experimental results with the simulation results. Li et al [9] conducted a triaxial unloading creep test on artificially frozen soil and described its creep characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al carried out triaxial tests on expansive soil and found that the soil showed shear shrinkage characteristics at the initial stage of stress loading. When soil enters the accelerated creep stage, its volume strain changes from shrinkage to expansion [17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the concept of a binary medium, Wang et al established a binary medium creep model suitable for frozen soil [24]. With the long-term research on the rheological theory of soil by various researchers, many previous rheological constitutive models applicable to geotechnical materials can be broadly classified into the following four types: the element model, the damage rheological model, the yield-surface model, and the empirical model [17,25]. The above four types of models are applicable to different working conditions and stress states.…”
Section: Introductionmentioning
confidence: 99%